The efficacy of local isolate of Entomopathogenic fungus Beauveria bassiana against potato tuber moth Phthorimaea operculella (Zeller) Lepidoptera: Gelechiidae under laboratory conditions - Huda Zuhair Al- Mammori; Sadiq Mohammed Ali Ali; Hadi Mezal Khudair Khudair (Kufa Journal for Agricultural Sciences)
In this laboratory study, the effect of different concentrations of local isolate of entomopathogenic fungus Beauveria bassiana against potato tuber moth Phthorimaea operculllella was evaluated. In addition, GC Mass technique was used to identify the chemical compounds in the crude filtrate, the most important of which are Phenol, Methane, Ethane of B. bassiana. The results showed that B. bassiana was significantly the highest efficacy against compared to fourth instar larvae of P. operculllella. Where the mortality rate was 41.67 and 32.96% when at a concentration of 7.5 g/L, respectively. The overall results indicated that the fungus has a high efficiency in affecting the eggs and larvae of the fourth instar of the insect, which can be used efficiently to reduce the infection rate in the insect and can be a promising method for insect control and plant protection.